(untitled) (The Research of Medical Science Review, 2025)
Background: Obstructive sleep apnea, marked by repeated upper airway blockage during sleep, often goes undetected in pregnancy due to inadequate history-taking and exams, leading to complications for both mother and baby. Objective: To assess the prevalence of high risk of obstructive sleep apnea and to assess the risk of obstructive sleep apnea and find out its association associated factors among pregnant women. Methodology: A Cross-sectional analytical study was conducted with a simple size of 144 pregnant women in Shaikh Zayed hospital of Lahore, Pakistan. Data was collected with help of Berlin Questionnaire to assess obstructive sleep apnea risk. Data was analyzed with help of SPSS 27 using a chi square test with p less than 0.05. Results: All participants were pregnant women aged 19–40 years, with an average height of 1.66 m and weight of 86.74 kg; most had two or more children. The prevalence of high-risk OSA was 52.08%, with significant associations found between OSA risk and height, weight, BMI, diabetes, gestational age, and number of children (p<0.05). No significant associations were observed for age, blood pressure, or residential area; 68, 63, and 50 women tested positive for OSA in categories 1, 2, and 3, respectively. Conclusion: The study found a 52.08% prevalence of high-risk OSA among pregnant women, significantly linked to BMI, diabetes, gestational age, and number of children. Early screening during routine visits is essential to reduce OSA-related complications.